Pemahaman Guru terhadap Wawasan Pendidikan dalam Perspektif Islam - Astuti, Windi Dwi; Rahmadia, Nurul Anisa; Mahdi, Khairunisa Halima Binti; Husna, Difa’ul (Lembaga Yasin AlSys, 2023)
Educational insight is the insight needed for the needs of teachers on issues related to their beliefs and in a more basic sense in terms of the behavior that all teachers have in carrying out tasks related to learning insights. The learning process is basically inseparable from the teacher's understanding of his students. This is because the teacher's opinion of these students forms the basis of their thinking and treatment of students. Then educational insight in an Islamic perspective aims to foster a balanced pattern of human character through mental development, brain intelligence, reasoning, feelings and senses. Then there are 4 (four) educational competencies covering educational, personality, professional, and social competencies. The ultimate goal of educational insight is essentially the embodiment and ideals of Islamic teachings with a mission for the welfare of mankind in this world and the hereafter.